Mutual impressions writers from the Americas reading one another - Stavans, Ilan. (Durham, NC Duke University Press, 1999)
I South reading North -- II North reading South.
South reading north: Prologue: Pedro Henrâiquez Ureäna -- Josâe Martâi on Walt Whitman -- Victoria Ocampo on John Steinbeck -- Alejo Carpentier on Herman Melville -- Carlos Fuentes on William Styron -- Jorge Luis Borges on Nathaniel Hawthorne -- Gabriel Garcâia Mâarquez on William Faulkner -- Hiber Conteris on Raymond Chandler -- Ezequiel Martâinez Estrada on Henry David Thoreau -- Ilan Stavans on Julia Alvarez -- Derek Walcott on V.S. Naipaul -- Josâe Bianco on Ambrose Bierce -- Antonio Benâitez Rojo on Lafcadio Hearn -- Juan Carlos Onetti on Vladimir Nabokov -- Mario Vargas Llosa on Ernest Hemingway -- Nicolâas Guillâen on Langston Hughes -- Octavio Paz on William Carlos Williams -- Pablo Neruda on Robert Frost -- Julio Cortâazar on Edgar Allan Poe -- North reading south: Prologue: John Barth -- John Updike on Augusto Roa Bastos -- Grace Paley on Clarice Lispector -- Katherine Anne Porter on Josâe Joaquâin Fernâandez de Lizardi -- Willam H. Gass on Jorge Luis Borges -- Mark Strand on Nicanor Parra -- Paul West on Alejo Carpentier -- Waldo Frank on Ricardo Gèuiraldes -- Barbara Probst Solomon on Teresa de la Parra -- Robert Bly on Pablo Neruda -- Kenneth Rexroth on Homero Aridjis -- Robert Coover on Julio Cortâazar -- Susan Sontag on Machado de Assis -- Thomas Pynchon on Gabriel Garcâia Mâarquez -- William Kennedy on Ernesto Sâabato.
Includes bibliographical references and index.
Also issued online.
Keywords: American literature -- History and criticism; Latin American literature -- Appreciation -- United States; Latin American literature -- History and criticism; American literature -- Appreciation -- Latin America; Amerikaans; Letterkunde; Receptie; Spaans; Aufsatzsammlung